Just prisons: requests and complaints in prisons in Europe - Daems, Tom; Larrauri Pijoan, Elena (Palgrave studies in prisons and penology, 2024)
Chapter 1. Taking complaints and requests in prisons seriously (Tom Daems and Elena Larrauri) -- Chapter 2. The Dutch Complaint Procedure for Prisoners Under Pressure (Sonja Meijer and Megan Jansen) -- Chapter 3. Who complains in prison, who doesn’t and why? A view from Germany (Christine Morgenstern and Mary Rogan) -- Chapter 4. Irish Prisoner Complaints: the challenges of complaining from within (Sophie Van Der Valk) -- Chapter 5. A new complaint system for prisoners in Belgium (Tom Daems) -- Chapter 6. The system of prisoners’ complaints in Romania: law vs. Practice (Cristina Dâmboeanu) -- Chapter 7. ‘They need to like you to get an answer’: Prisoners’ Perspectives on Requests and Complaints in Spanish Prisons (Elena Larrauri).